2014
DOI: 10.1074/jbc.m114.579185
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin-4 Is Required for Amoeboid-type Invasiveness of Melanoma Cells

Abstract: Background: Melanoma cells invasion through the dermis directly correlates with death, defining migration as critical. Results: ACTN4 down-regulation limits aggressive melanoma cells to a mesenchymal phenotype that retards collagen I matrix invasiveness. Conclusion: Amoeboidal morphology necessary for melanoma invasion requires ACTN4. Significance: This finding provides for a role of ACTN4 in melanoma invasion and implicates a linkage between actin cytoskeleton and melanoma progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…For example, mechanotransducing stress fibers, which dynamically form and dissolve during cell migration, are crosslinked largely by α-actinins and therefore could become more stable via α-actinin catch-bonding under load [36,37]. In addition to genetic diseases related to filamin B and α-actinin 4 mutations [ 38 , 39], increased expression of the mechanosensitive paralogs of α-actinin and filamin are strong negative prognosticators in multiple metastatic cancers [40][41][42]. Defining the mechanisms by which individual proteins and the network as a whole respond to force and determining which cytoskeletal elements are mechanosensitive is essential for elucidating normal mechanosensitive biological processes and identifying new targets for inhibiting aberrant processes in disease states.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mechanotransducing stress fibers, which dynamically form and dissolve during cell migration, are crosslinked largely by α-actinins and therefore could become more stable via α-actinin catch-bonding under load [36,37]. In addition to genetic diseases related to filamin B and α-actinin 4 mutations [ 38 , 39], increased expression of the mechanosensitive paralogs of α-actinin and filamin are strong negative prognosticators in multiple metastatic cancers [40][41][42]. Defining the mechanisms by which individual proteins and the network as a whole respond to force and determining which cytoskeletal elements are mechanosensitive is essential for elucidating normal mechanosensitive biological processes and identifying new targets for inhibiting aberrant processes in disease states.…”
Section: Resultsmentioning
confidence: 99%
“…Tenascin and other proteins are mainly at the edge of the advancing wound front wherein they establish a pro-migratory environment, serving also to enhance inflammatory cell adhesion and migration early in the healing process (28). These matricellular proteins in turn effect growth factor signaling through cryptic receptor binding motifs within the proteins themselves (matrikines), which signal via the EGF receptor to induce motility (15, 2931) In the same vein, these components also may contain growth factor binding sites that similarly regulate signaling, such as those found in fibronectin (32). As the fibroblasts immigrate and establish in the wound site, they produce collagen III and collagen I to provide further structural integrity to the matrix, with fibronectin acting in this important case as a scaffold for collagen deposition (33).…”
Section: A Changing Matrix During Repair and Regenerationmentioning
confidence: 99%
“…ACTN4, for example, plays multiple roles in influencing cellular morphology, yet the mechanisms by which it contributes to increased cancer invasion has not been resolved. Previous studies found that ACTN4 plays a major role in destabilizing focal adhesions in multiple cell types [34, 35]. The focal adhesion protein zyxin binds to the rod domain of ACTN4 and recruits it to nascent focal adhesions [26].…”
Section: Alpha-actinin In Metastatic Cancermentioning
confidence: 99%
“…The focal adhesion protein zyxin binds to the rod domain of ACTN4 and recruits it to nascent focal adhesions [26]. Overexpression of ACTN4 in melanoma cancer cell lines drives cellular morphology from a more mesenchymal type to an amoeboid type by reducing focal adhesion size [35]. In ACTN4 knockdown mouse fibroblasts, focal adhesions are fewer, yet larger, and spreading is increased, consistent with mesenchymal type cells [36].…”
Section: Alpha-actinin In Metastatic Cancermentioning
confidence: 99%
See 1 more Smart Citation